Psycoeducation of Responsible Scouts Care for Others in Disaster Response - I.G.A.A. Noviekayati; Eric Arizona Samudra; Carissa Valerie; Rizky Ariyanto; Mahardi Setia Barata (Journal Research of Social Science, Economics, and Management, 2021)
The attitude of disaster response to disaster-affected communities in general is an urgent priority to be given so that the community becomes resilient. So far, people are accustomed to relying on government assistance and are not able to provide an appropriate first response. This is because the community does not understand how to act appropriately when a disaster occurs in the area where they live. Law No. 24 of 2007 on Disaster Management. The subjects in this study were 110 Advanced Coaches, the Surabaya Kwarcab Helping Brigade, the Surabaya Kwarcab Care Scouts, the Surabaya Kwartir Branch Work Council using a knowledge scale on disaster response and psychoeducation related to Psychological First Aids. The results of the calculation of the t test (Paired Sample Test) obtained the results of t = 6.473 at p = 0.000. This means that between the pre-test and post-test of there is a very significant difference the experimental group in the knowledge of disaster response. The pre-test of the experimental group (Mean = 96.2553) was higher than the post-test of the experimental group (Mean = 88.5745), this indicates that PFA psychoeducation can increase knowledge about disaster response, thus indicating a significant relationship between psychoeducational independent variables. PFA with the dependent variable is knowledge about disaster response. The implication of this research is that it is expected to become an extension program so that it can increase knowledge related to disaster mitigation so that in the future members of the Rescue Brigadier can become the vanguard of disaster mitigation.